EXPRESSIVE SPEECH IN MOVIES IF MOTHER IS NOT MARRIED TO HER FATHER : Tindak Tutur Ekspresif Dalam Film Andai Ibu Tidak Menikah Dengan Ayah - Diana susmita; Desi sukenti (SOSIOEDUKASI, 2025)
This research is motivated by the importance of language as a means of conveying messages and emotional expression in social interactions, including through film media. Pragmatic studies, especially expressive speech acts, play a role in understanding the speaker's psychological attitudes reflected in speech. The film If Mother Is Not Married to Dad by Kuntz Agus was chosen because it contains emotional dynamics and family conflicts that reflect the intense use of expressive speech. This research aims to identify, analyze, and interpret the forms of expressive speech that appear in film dialogue. The research uses a qualitative approach with a content analysis method. Data in the form of expressive speech obtained through documentation, listening, and recording techniques to all 119-minute film dialogues. Data analysis was carried out through reduction, categorization, presentation, and conclusion drawing using the classification of expressive speech acts according to Searle.The results showed that there were 48 data on expressive speech actions divided into 7 types of functions, with the dominance of expressing disappointment/regret as many as 15 speeches (31.25%) and affection/love as many as 10 speeches (20.83%). This expressive dominance reflects the film's main themes of inner conflict, emotional tension, and family sacrifice. These findings confirm that film serves as a powerful medium of psychological and social representation through language expression. This research provides novelty in the form of mapping the function of expressive speech in contemporary Indonesian film works as a source of pragmatic data and a theoretical contribution to the development of speech action studies in the audiovisual realm. The results of the research are expected to be a reference for pragmatic learning and a foothold for further research on speech actions in the family drama film genre.